Prevalence of smoking in the College of Health Services of Firat University - Pirinçci, Edibe; Erdem, Ramazan (My University, 2003)
Cigarette smoking frequency is generally at a high level in our country. Although they are aware of the risks of smoking, smoking prevalence among the health students is high and the trend of cessation is low. Behavior in this group is very important because they form an example to the community. The aim of this study is to examine the prevalence of smoking and some relational factors among students in the College of Health Services, Firat University in Elazi?. This study was carried out at the programs of medical documentation and secretary, medical laboratory, anesthesia, radiology in the college of Health Services. In June 2001-2002, there were 166 students in the college and 162 of them were reached. 43.8% of the students were female and 56.2% of them were male. Respondent's age ranged from 19 to 25 with the average age being 21.85. Most of the students were single (95.1%). It was found that 31.5% students of all respondents never smoked, 18.5% tried but didn't smoke, 8.6% were ex-smokers and 41.4 % were current smokers. 29.9% of current smokers smoked 20 or more cigarettes, 16.4% smoked 19 or less cigarettes per day. 46.3% of them have smoked everyday and the rate of occasional smokers were 53.7%. The rate of smoking for male was 51.6% and female was 28.2%. İn the educational level of the students' fathers, 9.5% of illiterate-literate group were smoking. This rate is 40.5% for high-school-university level (p>0.05). Most of the students (91.9%) totally agreed with the hazardous health effect of smoking. For this reason, the relation of cigarette and health should notice in the educational programs. Also in quit smoking campaign can give some help in regression of the smoking epidemic and the struggle against cigarette smoking.
Firat Üniversitesi Sa?lik Hizmetleri Meslek Yüksekokulu Ö?rencilerinde Sigara Kullanim Sikli?i
Keywords: Prevalence; Smoking; University students